Patient's care bundle benefits to prevent stroke associated pneumonia: A meta-analysis with trial sequential analysis - Guo, Feng; Fan, Qiao; Liu, Xiaoli; Sun, Donghai (Frontiers in Neurology, 2022)
Background: Patient’s care bundle has been found to have the beneficial effect on refractory diseases, but the preventive effect of this strategy on stroke-associated pneumonia (SAP) remains unclear. The purpose of this meta-analysis was to determine the role of the patient’s care bundle in the prevention of SAP. Methods: A systematic search was conducted in five electronic databases to identify randomized controlled trials (RCTs) published before 31 January, 2022. The incidence of SAP and aspiration and the length of hospital stay were assessed. Random pair-wise meta-analysis was conducted using Review Manager 5.4, and trial sequential analysis (TSA) was also performed. Results: Twenty eligible RCTs involving 1916 patients were included for data analysis. Pooled results suggested that patient’s care bundle was associated with significantly lower incidence of SAP (risk ratio [RR], 0.37; 95% confidence interval [CI], 0.29 to 0.46; p<0.001; I2=0%) and aspiration (RR, 0.23; 95% CI, 0.15 to 0.35; p<0.001; I2=0%). Meanwhile, patient’s care bundle also significantly shortened the length of hospital stay for general patients (mean difference [MD], -3.10; 95% CI, -3.83 to -2.37; p<0.001; I2=16%) and the length of intensive care unit (ICU) stay for patients with severe stoke (MD, -4.85; 95% CI, -5.86 to -3.84; p<0.001; I2=0%). Results of TSA confirmed that none of the findings could be significantly reversed by future studies. Conclusions: The patient’s care bundle effectively prevent the occurrence of SAP and aspiration, and shorten the hospital stay of stroke patients. However, it is necessary to design more high-quality studies to further validate our findings and investigate their applicability in other geographical regions.